(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: In order to find out the current situation of using electronic entertainment devices when eating children under 6 years old in Vietnam in 2021 in the context of the COVID-19 pandemic, we conducted a study: Using electronic entertainment devices when eating by children under 6 years old in Vietnam in 2021 and some related factors. Methodology: Cross-sectional description of 306 primary caregivers for children from June 1, 2021 to August 31, 2021. Convenient sampling method, collected by online questionnaires via KoboToolbox software shared on several Facebook groups. Result: There are 69.61% of children under the age of 6 use electronic entertainment devices during meals, most of them use electronic devices during the eating process, of which male children account for 73.30%, and girls account for 59.30%. Regarding the frequency of using electronic devices when eating by children, 49.77% of children regularly use electronic devices when eating; 37.56% of children use it occasionally; 9.39% of children always use it during meals and only 3.29% of children rarely use electronic devices when eating. Male children have a higher risk of using 2.36 times than female children, this result is statistically significant with OR=2.36 and 95%CI=1.38-4.05. Conclusion: During the time of social distancing due to the impact of the COVID-19 pandemic, the rate of children using electronic entertainment devices while eating is at a high level. Therefore, parents or primary caregivers of children need to limit the use of screens for their children during meals to prevent health problems for children.